The Influence of Work Motivation and Work Discipline on Employee Performance at PT Ariabima Propertindo - Al Qusaeri, Muammar Afif; Khasbulloh, M. Wahab; Khasanah, Muthi’atul (CV. Civiliza Publishing, 2025)
This research investigates the effect of work motivation and work discipline on employee performance at PT Ariabima Propertindo. The study is grounded in the recognition of these two factors as essential for enhancing workforce effectiveness and productivity in achieving organizational objectives. A quantitative approach was employed, utilizing questionnaires distributed to respondents based on the predetermined population. The collected data were analyzed through multiple regression techniques to assess the relationships and impacts among variables. The findings reveal that work motivation, driven by both internal and external factors, exerts a significant and positive influence on employee performance. Likewise, work discipline contributes by ensuring compliance with organizational policies, promoting punctuality, and supporting consistent task completion. When applied together, motivation and discipline play a substantial role in improving overall employee performance.